INCREASE OF ENERGETICALLY EFFICIENCY FOR THERMAL ACTIVATION OF BAUXITES - Bashliy, Sergey; Kovalenko, Viktor; Artemchuk, Viktor; Levchenko, Sergey; Vodennikova, Oksana (Scientific Journal "Metallurgy", 2021)
The modern state and question of decline of power charges and mined-out unit cost is considered due to perfection of technologies in the sphere of booty and production of alumina and aluminium. Possibility of the use of generator gas, which is able to provide a deserving competitive base for the alternative, traditional types of fuel is presented. Technology of application of generator gas which is foremost obtained from cheap biological mass (as a basic source for gasification unlike the liquid kinds of fuel) is offered, and такох allows to decide the row of contiguous questions: utilization of waste-woods, offcuts of agricultural productions, brown coal, rubber, but other A physical design is described during the lead through of full factor experiment in the conditions of realization of the stage of burning-out of bad quality table of contents of aluminium raw material at its processing on a method «Thermochemistry-Bayer». Analytical researches of temperature condition of process of the thermal activating of bad quality bauxite are conducted and physical and chemical transformations of material are described on every stage of experiment. It is created and a method and foot-pace algorithm of analytical calculation is described in detail of theoretical temperature of burning is created and described taking into account dissociation aquatic pairs and to carbon dioxide with application of method of successive approaching. It is developed recommendation for modernizations of the system of heating of tubular circulating stove for thermal activating bauxites. Possibility of passing of furnace on heating of natural gas is considered on an alternative fuel – generator synthesis-gas. Financial viability of the offered modernization is well-proven.